Do sit-to-stand performance changes during gait acquisition? - Alana Maria Ferreira Guimarães Bastos; Carolina Souza Neves da Costa; Nelci Adriana Cicuto Ferreira Rocha (Universidade Estadual Paulista (UNESP), 2014)
In a child's daily routine, sit-to-stand (STS) is a prerequisite activity for many functional tasks. The relationship between gait and other abilities has been pointed out by many authors, but there is no study investigating the changes in STS during gait acquisition in children. The purpose of this study was to analyse, in healthy children, changes that occur in STS performance during gait acquisition. Five healthy children were initially assessed with an average age of 13.6 months. The kinematics in STS movement performance of the children was evaluated longitudinally during different periods of walking experience: children who have not acquired independent walking, 8.2 (±8.4) days of independent walking experience, and 86.2 (±8.7) days of independent walking experience. At the gait acquisition period we found a significant decrease in the final trunk flexion angle and an increase in amplitude of the trunk flexion. The walking experience may have changed the execution of the STS movement.